Sotagliflozin, a Dual SGLT1/2 Inhibitor, Improves Cardiac Outcomes in a Normoglycemic Mouse Model of Cardiac Pressure Overload - Young, Sophia L.; Ryan, Lydia; Mullins, Thomas P.; Flint, Melanie; Steane, Sarah E.; Walton, Sarah L.; Bielefeldt-Ohmann, Helle; Carter, David A.; Reichelt, Melissa E.; Gallo, Linda A. (Frontiers in Physiology, 2021)
Selective SGLT2 inhibition reduces the risk of worsening heart failure and cardiovascular death in patients with existing heart failure, irrespective of diabetic status. We aimed to investigate the effects of dual SGLT1/2 inhibition, using sotagliflozin, on cardiac outcomes in normal diet (ND) and high fat diet (HFD) mice with cardiac pressure overload. Five-week-old male C57BL/6J mice were randomized to receive a HFD (60% of calories from fat) or remain on ND for 12 weeks. One week later, transverse aortic constriction (TAC) was employed to induce cardiac pressure-overload (50% increase in right:left carotid pressure versus sham surgery), resulting in left ventricular hypertrophic remodeling and cardiac fibrosis, albeit preserved ejection fraction. At five weeks into the dietary protocol, mice were treated for seven weeks by oral gavage once daily with sotagliflozin (10mg/kg body weight) or vehicle (0.1% tween 80). In ND mice, treatment with sotagliflozin attenuated cardiac hypertrophy and histological markers of cardiac fibrosis induced by TAC. These benefits were associated with profound diuresis and glucosuria, without shifts toward whole-body fatty acid utilisation, increased circulating ketones, nor increased cardiac ketolysis. In HFD mice, sotagliflozin reduced the mildly elevated glucose and insulin levels but did not attenuate cardiac injury induced by TAC. HFD mice had vacuolation of proximal tubular cells, associated with less profound sotagliflozin-induced diuresis and glucosuria, which suggests dampened drug action. We demonstrate the utility of dual SGLT1/2 inhibition in treating cardiac injury induced by pressure overload in normoglycemic mice. Its efficacy in high fat-fed mice with mild hyperglycemia and compromised renal morphology requires further study.